The boondock saints - Duffy, Troy; Flanery, Sean Patrick; Reedus, Norman; Dafoe, Willem; Dana, Jeff; Brood Syndicate; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2001)
When the Russian mob starts to muscle its way into a South Boston Irish neighborhood, two brothers embark on a campaign to kill the evil doers, believing God is directing them.
Originally released as a motion picture in 1999.
Features: audio commentary, interactive menus, director and cast filmographies, deleted scenes, trailer, scene selections and outtakes.
Director of photography, Adam Kane; production design, Robert De Vico; editor, Bill Deronde; music, Jeff Dana.
Sean Patrick Flanery, Norman Reedus, Willem Dafoe, David Della Rocco, Billy Connolly.
MPAA rating: R.
DVD Dolby digital surround stereo.
Keywords: Russian American criminals -- Massachusetts -- Boston -- Drama; Irish American criminals -- Massachusetts -- Boston -- Drama; Divine commands (Ethics) -- Drama; Gangster films; Video recordings for hard of hearing people; Feature films